Problematika Motivasi Belajar Bahasa Arab di MA Darussalam Maguwoharjo Sleman dalam Konteks Psikolinguistik - Maulida, Farhati (Study Program of Arabic Language Teaching, 2021)
This study aims to explain the methods and strategies of learning Arabic elements. The research approach used in this study is the qualitative approach. The type of research uses field research. In this case, researchers searched for data by reading and tracing from several books, journals and other literature. In this study, the authors used descriptive qualitative analysis. This study aims to identify the motivation of Arabic language learning in MA Darussalam Maguwoharjo. Paradigm research used is post-positivism with qualitative approach and this type of research case study. The data source consists of primary data, namely Aarab language teacher and Ma Daarussalam Maguwoharjo student, and secondary data in the form of supporting documents. The motivation of Arabic language learning in MA Daarussalam Maguwoharjo consists of learning methods, learning techniques, teacher competence, time allocation, learning facilities, and media are not all optimal, when all are related to each other in determining whether or not the Arabic language defence Lujan in MA Daarussalam Maguwoharjo. The problem of Arabic language learning motives is associated with the background of hydrogen students, students' learning interests, lack of student feedback. The problem related to teachers is the lack of use of facilities and media among Teachers Arabic Language. Issues related to methods in learning consist of the lack of precise methods used, the lack of variation of plans in learning. While the problem related to time and facilities or media is the allocation of time is minimal and sometimes less conducive, as well as facilities and facilities that are less dissected.